CONFLICT ANALYSIS IN MOTHER DAUGHTER RELATIONSHIP IN OKKY MADASARI'S THE YEARS OF THE VOICELESS - Nisa Wiratie Wulantama, - (2022)
Conflict is an inevitable event that always occurs in human life as well in literary works. Okky Madasari's The Years of the Voiceless shows conflicts that happen to a mother and a daughter who need to fight for women's rights in the male-dominated world in the post-colonial era in Indonesia. They live based on their faiths and beliefs that are different due to the generational gap. By implementing close-reading method based on the New Criticism that is discussed by Tyson (2006), this study is only looked into the intrinsic elements of the text to discover the sources of the conflict between mother and daughter and the way the conflicts are resolved. The results of the study reveal that the conflicts which affect the mother-daughter relationship originate from external and internal conflicts. The conflicts are resolved through changes in the daughter's character. This study demonstrates that the generational gap, society, and characters' personalities are the main causes of conflict in the mother-daughter relationships. The findings of this study also suggest that the conflicts give effects to the mother-daughter relationship.